If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x+14=0
We simplify the equation to the form, which is simple to understand
4x+14=0
We move all terms containing x to the left and all other terms to the right.
+4x=0-14
We simplify left and right side of the equation.
+4x=-14
We divide both sides of the equation by 4 to get x.
x=-3.5
| x^2-37x+25=34 | | =b^4+.9549296586*b^2-2.735671958 | | =3*b^4+5.729577951*b^2-8.207015875 | | 10y^2+3y-7=0 | | 2x-5=6x | | =b^2+1.382b-1.654 | | =b^4+1.909859317*b^2-8.594366927 | | 3(3x-1)=4(3x+1) | | x^3-11x^2+24x=3 | | 4-9a^2= | | (2x-5)=(x+30) | | 2(v-4)=8v+34 | | -2xy*3xy= | | 8-4x-(12-3x)= | | 80-(4x+7)=4(x+7)+x | | 2(2x-1)=3(x+1) | | x+73x=77 | | 6b^2+19b-36=0 | | 6(d+6)=4(d-6)-d | | -24(x-2)= | | 2(n+4)=8-6(n-4) | | -24(x+2)= | | -12(2x-12)= | | 2x-2y=-1 | | m+m(0.07)= | | 2x-3y+x+5y-3= | | y=5x-13 | | (57x+58y)+(-5x+41y)= | | (18x+2y)+(36x+27y)= | | (63x+50y)-(17x+35y)= | | (64x+48y)-(9x-16y)= | | 5x-3=-10x+8 |